2010
DOI: 10.1021/om100246j
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II) Complexes Bearing Chelating Cyclopentadienyl-N-Heterocyclic Carbene Ligands as Catalysts for Hydrosilylation and Hydrogen Transfer Reactions

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
121
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 42 publications
3
121
0
Order By: Relevance
“…In addition to the abovementioned substrates, we examined the reduction of 3'-nitroacetophenone, and found that this particular ketone reacted poorly giving only 20% yield of the corresponding alcohol after 24 h. Nitroacetophenones are known to be problematic in iron-catalyzed hydrosilylations as shown, for instance, by Royo and co-workers. [16] Overall, with the exception of 3'-nitroacetophenone, the catalytic system performed well for all examined substrates and the alcohols were obtained in good to excellent yields within a rather short reaction time (0.5 to 3 h) using a catalytic loading of 1 mol% iron acetate.…”
Section: H T U N G T R E N N U N G [Hemim]a C H T U N G T R E N N Umentioning
confidence: 80%
See 1 more Smart Citation
“…In addition to the abovementioned substrates, we examined the reduction of 3'-nitroacetophenone, and found that this particular ketone reacted poorly giving only 20% yield of the corresponding alcohol after 24 h. Nitroacetophenones are known to be problematic in iron-catalyzed hydrosilylations as shown, for instance, by Royo and co-workers. [16] Overall, with the exception of 3'-nitroacetophenone, the catalytic system performed well for all examined substrates and the alcohols were obtained in good to excellent yields within a rather short reaction time (0.5 to 3 h) using a catalytic loading of 1 mol% iron acetate.…”
Section: H T U N G T R E N N U N G [Hemim]a C H T U N G T R E N N Umentioning
confidence: 80%
“…[15] In addition, Royo and coworkers demonstrated that similar iron complexes containing a tethered N-heterocyclic carbene (NHC) ligand catalyzed the reduction of aldehydes under hydrosilylation conditions. [16] The latter two studies demonstrate that N-heterocyclic carbenes, which are frequently used as ligands in various catalytic applications, [17] also are effective in iron-catalyzed hydrosilylations.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30]. [33,34] despite the presence of the sterically demanding N-heterocyclic carbene-functionalized cyclopentadienyl ligand, while…”
Section: (Thf)][bf 4 ]mentioning
confidence: 99%
“…[1][2][3][4][5] In order to render catalytic hydrogenation reactions more efficient, many efforts have been made to decrease the costs for these reactions either by obtaining highly active catalytic species or by substituting inexpensive metals such as iron for the commonly used noble metals Pd and Pt. [6][7][8][9][10] The broad availability of iron makes it a desirable metal for catalysis. Furthermore, iron compounds are usually easy to handle and toxicologically inert.…”
mentioning
confidence: 99%